Effects of encapsulated Lactobacillus acidophilus along with pasteurized longan juice on the colon microbiota residing in a dynamic simulator of the human intestinal microbial ecosystem - Chaikham P. (2014)
The effect of encapsulated Lactobacillus acidophilus LA5 along with pasteurized longan juice on the colon microbiota was investigated by applying a dynamic model of the human gastrointestinal tract. Encapsulated L. acidophilus LA5 in pasteurized longan juice or sole encapsulated L. acidophilus LA5 exhibited the efficiency of colonizing the colon and enabling the growth of colon lactobacilli as well as beneficial bifidobacteria but inhibited the growth of fecal coliforms and clostridia. Moreover, these treatments gave rise to a significant increase of lactic acid and short-chain fatty acids such as acetate, propionate, and butyrate. Although acetate displayed the highest quantity, it was likely that after incorporating encapsulated L. acidophilus LA5 plus pasteurized longan juice, quantity of butyrate exceed propionate, and acetate in comparison with their controls. Denaturant gradient gel electrophoresis patterns confirmed that various treatments affected the alteration of microbial community within the simulator of the human intestinal microbial ecosystem. © 2013 Springer-Verlag Berlin Heidelberg.